2006
DOI: 10.1002/fuce.200600002
|View full text |Cite
|
Sign up to set email alerts
|

Internal Reforming of Methane at Ni/YSZ and Ni/CGO SOFC Cermet Anodes

Abstract: The internal reforming of methane on Ni/CGO and Ni/YSZ anodes was investigated with single cells operated at steam to carbon ratios from 0 to 3 and at temperatures of 800 °C and 950 °C. The incorporation of gas extraction ports allowed the measurement of the local gas composition in the anode gas compartment by gas chromatography. The methane conversion is presented as a function of feed gas composition, temperature, gas flow velocity, and electrical load. The impact of the anode material on the reforming reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 10 publications
3
57
3
Order By: Relevance
“…Since both the microstructure of a Ni/YSZ anode (porosity, tortuosity, anode thickness, Ni grain size, Ni surface area) and the conditions of the according flow field have a large influence, measurements have to be carried out under appropriate operating conditions in order to determine the valid formal kinetics. For a methane-rich operating gas under internal reforming conditions such investigations have been performed by Ahmed and Foger [11] and Timmermann et al [17]. However, no investigations have been reported so far for Ni/YSZ anode structures that correspond e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Since both the microstructure of a Ni/YSZ anode (porosity, tortuosity, anode thickness, Ni grain size, Ni surface area) and the conditions of the according flow field have a large influence, measurements have to be carried out under appropriate operating conditions in order to determine the valid formal kinetics. For a methane-rich operating gas under internal reforming conditions such investigations have been performed by Ahmed and Foger [11] and Timmermann et al [17]. However, no investigations have been reported so far for Ni/YSZ anode structures that correspond e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Although numerous studies, both experimental and theoretical, suggest that the ionic conductivity of the electrolyte within composite SOFC electrodes can be very important for electrode performance, we are unaware of any systematic investigations on this topic. For example, while it has been demonstrated that the substitution of YSZ in Ni-YSZ anodes with doped ceria results in performance enhancement, [29][30][31][32] it remains uncertain whether this is due to the higher ionic conductivity of ceria or to the fact that ceria possesses significant catalytic activity for the electrode reaction. That catalytic activity may be responsible is suggested from the results of Sumi, et al who compared the performance of Ni-YSZ and Ni-ScSZ (scandia-doped zirconia) anodes.…”
mentioning
confidence: 99%
“…(1) and (2), respectively. However, the water gas shift reaction has been frequently reported to remain in the thermodynamic equilibrium during the DIR process, thus, the MSR reaction has been the focus of researches [3,11,18].…”
Section: Introductionmentioning
confidence: 99%